2001
DOI: 10.1002/1097-0142(20011015)92:8<2172::aid-cncr1560>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

A lipophilic vasoactive intestinal peptide analog enhances the antiproliferative effect of chemotherapeutic agents on cancer cell lines

Abstract: BACKGROUND Vasoactive intestinal peptide (VIP) is one of several small neuropeptides that affect cancer growth. A lipophilic VIP analog, stearyl‐Nle17‐neuroten‐ sin6‐11VIP7‐28 (SNH) that inhibited lung carcinoma growth has been described previously. The experiments performed were clonogenic assays in vitro and tumor xenografts in nude mice in vivo. These studies were now extended to colon carcinoma and to combination therapy with chemotherapeutic agents. METHODS Assays were performed with cell lines, and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…VPAC 1 in myenteric nerve fibers is likely to function as autoreceptor, regulating the release of VIP and PACAP. VPAC 2 in neuroendocrine cells may also function as autoreceptor, which may explain the high levels of internalized receptors detected in these (2,3,(27)(28)(29)(30)(31)(32)(33). Whereas growth-promoting activities have been reported for VIP, growth-inhibiting properties have been found for VIP antagonists in various tumor models (2,3,(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VPAC 1 in myenteric nerve fibers is likely to function as autoreceptor, regulating the release of VIP and PACAP. VPAC 2 in neuroendocrine cells may also function as autoreceptor, which may explain the high levels of internalized receptors detected in these (2,3,(27)(28)(29)(30)(31)(32)(33). Whereas growth-promoting activities have been reported for VIP, growth-inhibiting properties have been found for VIP antagonists in various tumor models (2,3,(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Second, VIP/PACAP receptor-positive intestinal and endocrine tumors can be visualized by in vivo VIP receptor scintigraphy (1,4,6,(23)(24)(25)(26). Third, application of VIP and PACAP analogs modulates tumor growth in animal models (2,3,(27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Basic amino acids of VIP such as Arg 14 , Lys 15 and Lys 21 may interact electrostatically with acidic amino acids such as Glu 36 on the VPAC 1 -R [36]. Substitution of Ala for VIP amino acids at positions 1, 6, 12, 14 or 23 reduced binding affinity to VPAC 1 -R by over 2-orders of magnitude [19,36].…”
Section: Discussionmentioning
confidence: 99%
“…VIP receptor antagonists such as VIPhybrid or (N-Stearyl 1 , Nle 17 )VIP not only inhibit the proliferation of lung and breast cancer cells [17,34], but they potentiate the cytotoxicity of chemotherapeutic agents [14,31]. The overexpression of peptide receptors by the tumor can be used for receptor-targeted delivery of peptide receptor cytotoxic agents [35].…”
Section: Introductionmentioning
confidence: 99%
“…This attenuation of tumor proliferation was proven to be receptormediated as the VIPhybrid inhibited the specific 125 I-labeled VIP binding to NSCLC cell lines (14). It was also demonstrated that the VIPhybrid potentiates the cytotoxicity of chemotherapeutic agents in cancer cell lines (15). Vasoactive intestinal peptide/growth hormone-releasing hormone (VIP/ GHRH) antagonists, such as JV-1-52 and JV-1-53 constructed by our group, were also able to inhibit the growth of androgenindependent prostate cancers by abrogating the autocrine/ paracrine mitogenic stimuli of VIP (16).…”
Section: Introductionmentioning
confidence: 99%